(3GdaQb Hjf GdXGA hGdVGOs - (3SYO Hf Ydj Hf eMeO GdRfLGfj, CHh GdbGSes ((3eSYhO Hf SYjO Hf YHO Gddg GdehUdi s)
(3ChdgG (B:s
(3CNHQ GdTjN CHh eMeO YHO GddWja bGd CNHQfG CHh GdbGSe bGd (B: (3gPG HGH eYQaI eG jcJH HGdVGA hGdXGA eYkG hGdaQb HjfgeG ai GdNW hGdgLGA s
(3BNQgG (B:s
(3hGdJbQjV HGdVGO (B: (3GTYQ , hGdJYhjV CjVkG LQI GdHYjQ EPG eVagG Ke QOgG Edi Mdbg Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HBNQgG bQGAI GdfGSN Ydi YHO GddWja Hf jhSa Hf eMeO GdHZOGOi GdfMhi hELGRI GdCNjQ dg cJHgG YHO GddWjas
(3HgG fXGe GdJYbjHIs
(3cJHJ HNW ajg VHWs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GddZIs